Intra-individual and crossover effects of work contact in leisure time on satisfaction with work-life balance - Yvonne Lott (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2018)
Using data from the 2015/2016 German Family Panel (pairfam), this article examines the intra-individual and crossover effects of work contact in leisure time on satisfaction with work-life balance. Results of mediation analyses show that individuals who have work contact in leisure time are less satisfied with their work-life balance because of the (perceived) obligation to be available after work hours. Partners, by contrast, are less satisfied with work-life balance only when the other partner actually has work contact in leisure time. The negative association between work contact/availability and satisfaction with work-life balance is mediated in both partners by work-home conflict.
Keywords: 330